Examination of stress distribution and fracture resistance in five-unit tooth- nd implant-supported partial fixed zirconia prosthesis - Guven, Sedat; Aguloglu, Suleyman; Beydemir, Koksal; Dundar, Serkan; Atalay, Yusuf; Ucan, Musa Can; Asutay, Fatih (Taylor & Francis Ltd, 2015)
In this study, stress distribution and fracture strength values of zirconia frameworks were compared in five-unit tooth- and implant-supported fixed zirconia prosthesis. Three-dimensional finite element stress analysis and static non-linear analysis were used. Because of the boundary conditions determined for these methods, the tooth- and implant-supported models only included the regions of tooth numbers 43-47. The highest stress value (901.845 MPa) was measured in Model 1 (five-unit tooth-supported fixed zirconia bridge) at the mesial gingival neck area of restoration number 45. This stress value was within the ultimate strength of zirconia (900-1200 MPa). Stress values for connector regions were not in the ultimate strength value of zirconia. Stress values in the tooth-supported fixed zirconia bridge were more than the values in the implant-supported fixed zirconia bridge. The highest stresses in Model 2 (five-unit implant-supported fixed zirconia bridge) occurred in the restoration that the model was installed on. The obtained results showed that five-unit tooth-supported posterior zirconia fixed bridge prostheses are not recommended and that the second premolar region is most seriously affected in terms of stress.
Keywords: finite element analysis; implant-supported prosthesis; tooth-supported prosthesis; connector regions; zirconia framework